Advance Directives of German People with Parkinson’s Disease Are Unspecific in regard to Typical Complications - Martin Klietz; Özlem Öcalan; Nils Schneider; Dirk Dressler; Stephanie Stiel; Florian Wegner (Parkinson's Disease)
Parkinson’s disease (PD) is a progressive neurodegenerative movement disorder with an increased morbidity and mortality. People with PD (PwP) may suffer from decreased quality of life due to various motor and nonmotor symptoms. To a huge proportion, PwP have written an advance directive (AD); however, the content of these forms in regard to PD-specific complications is unclear. The aim of this study was to qualitatively and quantitatively analyze ADs of PwP in Germany. ADs of PwP were analyzed in a German sample of members of the German PD patient association. Participants completed a questionnaire about their AD and sent a copy of their AD to the study center for detailed analyses. ADs were qualitatively and quantitatively analyzed for general and PD-specific aspects and usefulness concerning treatment decisions. 82 PwP were included in the study, and in 76, an AD could be analyzed. Family members, notaries, lawyers, and general physicians mainly counseled writing of the ADs. 4 PwP consulted a neurologist to establish a specific AD for PD. In the analysis, ADs displayed a good specificity for general aspects, but they were unspecific to PD in the vast majority of cases. PwP should be encouraged to create an AD early in their disease and adapt it in the course of the disease. PD-specific aspects for an AD could be details in relation to dopaminergic therapies at the end of life, management of non-oral advanced therapies, neuropsychiatric symptoms, dementia, and swallowing disturbances.